Impact of a Strained Periodic Multilayer on the Surface and Crystal Quality of a Semipolar (11–22) GaN Template - Makinudin, Abdullah Haaziq Ahmad; Omar, Al-Zuhairi; Anuar, Afiq; Shuhaimi, Ahmad; DenBaars, Steven P.; Supangat, Azzuliani (American Chemical Society, 2019)
Efficient reduction of defects and dislocations in a semipolar (11-22) GaN epilayer with the use of an AlN/GaN strained periodic multilayer is demonstrated. On- A nd off-axis X-ray rocking curve analyses have shown significant improvement in the crystalline qualities with remarkable narrowing in their respective full width at half-maximum upon utilization of increased AlN/GaN pairs. X-ray reciprocal space mapping revealed a prominent increment in the degree of relaxation state, with notable shrinkage in the diffuse scattering streak. Structural evaluation via transmission electron microscopey illuminates the interruption of defect and dislocation propagation due to the strained periodic multilayers. It was observed that the first 20th pairs exhibited a three-dimensional growth mode owning to numerous defects originating from the AlN/sapphire interface. Such a phenomenon was found to have a positive impact toward accumulating the propagation of defects. The surface morphology analysis elucidates the reduced stripe-like undulations, whereby the terrace-like features in the lower scales endured an enhanced rearrangement favoring the reduced defect density. © 2019 American Chemical Society.